Malaysian government initiatives in managing education crisis during COVID-19 pandemic / Nur Atika Azman ... [et al.] - Azman, Nur Atika; Abd Aziz, Nur Aniessa; Azmi, Muhammad Syahmizan (2021)
Education has always been recognized as a crucial tool to exhume inner potentials of individuals. The Malaysian government for the past decades has persistently and effectively emphasized on the significant roles of education in human development. The unwavering efforts can be seen manifested in the implementation of national ecucation programs and policies throughout the nation. The Malaysian Education Blueprint (2013-2025) for instance, is one of the initiatives of the Ministry of Education to energize the Malaysian education system. This blueprint supports the Philosophy of National Education to ensure Malaysian education continuously develops overall individual potentials and integrate them to create a set of balanced qualities in terms of intellectual, spiritual, emotional, and physical capabilities which are directly aligned to achieving United Nation Sustainable Development Goal (SDG) no 4 ; Quality education (National Education Policy, 2017). The COVID-19 oubreak has undeniably created some distraction in education sector and force the entire educational system to embrace a new normal. According to The World Economic Forum (WEF), the acceleration of Covid-19 cases during the pandemic have made nations worldwide act to the closed educational institution to minimize the total daily infection. To curb COVID-19 infection, the government is enforcing Movement Control Order (MCO) (Aziz, 2020), with mandatory strict restrictions on population, including the closure of offices, schools, universities with "Just stay at home" command (Sheena Kaur, 2020). Since mid-March 2020, school closures have suspended formal classroom learning for 4.9 million preschools, elementary and middle school students across the country (Khazanah Research Institute, 2020). Online learning has been implemented as one of undisputable means in exercising teaching and learning process at many levels, be it schools or universites. However, the issues of affordability to use highly effecient electronic devices and internet data among the students have become a debate.